2017
DOI: 10.1093/toxsci/kfx098
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of As2O3-Induced Action Potential Prolongation and Using hiPS-CMs to Evaluate the Rescue Efficacy of Drugs With Different Rescue Mechanism

Abstract: Arsenic trioxide (As2O3) has been verified as a breakthrough in the management of acute promyelocytic leukemia in recent decades. However, cardiotoxicity, especially long QT syndrome (LQTS) has become the most important issue during As2O3 treatment. The characterized mechanisms behind this adverse effect are inhibition of cardiac hERG channel trafficking and increase of cardiac calcium currents. In our study, we found a new pathway underlying As2O3-induced cardiotoxicity that As2O3 accelerates lysosomal degrad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(29 citation statements)
references
References 42 publications
1
28
0
Order By: Relevance
“…Lysosomal and proteasome degradation of hERG on the plasma membrane were accelerated during As 2 O 3 -induced cardiotoxicity. Further research showed that As 2 O 3 decreased the caveolin-1 level, which accounted for As 2 O 3 -triggered hERG degradation (Yan et al, 2017). Certainly, some CMM can also affect potassium channels by suppressing I to , I k1 , I kur , and I kATP .…”
Section: Potassium Channelsmentioning
confidence: 94%
“…Lysosomal and proteasome degradation of hERG on the plasma membrane were accelerated during As 2 O 3 -induced cardiotoxicity. Further research showed that As 2 O 3 decreased the caveolin-1 level, which accounted for As 2 O 3 -triggered hERG degradation (Yan et al, 2017). Certainly, some CMM can also affect potassium channels by suppressing I to , I k1 , I kur , and I kATP .…”
Section: Potassium Channelsmentioning
confidence: 94%
“…Neonatal rat ventricular myocytes (NRVMs) were isolated from dissected hearts of 1-2-day-old neonatal Sprague-Dawley rats (provided by the Experimental Animal Center of the Second Affiliated Hospital of Harbin Medical University, China). Cardiomyocytes were cultured as described previously [18].…”
Section: Methodsmentioning
confidence: 99%
“…Hsu et al 75 used four independent hiPSC-CM lines to examine the mechanism of increased DIC in the presence of lapatinib. Other studies have used single hiPSC-CM lines to characterize CAEs caused by doxorubicin, 58,[76][77][78][79][80][81][82][83][84] trastuzumab, 58,85,86 etoposide, 87 arsenic trioxide, 84,88,89 TKIs, [90][91][92][93][94][95][96] and histone deacetylase inhibitors. 84,97,98…”
Section: Hipscs In Pharmacogenomics Researchmentioning
confidence: 99%